Hubungan Pengetahuan, Sikap dan Sumber Informasi Dengan Perilaku Personal Hygiene Saat Menstruasi Pada Remaja Puteri di SMK Negeri V Buru Selatan, Maluku Tahun 2022 - Nanik Yuliwati; Fitri Solissa (Jurnal Ilmiah Wahana Pendidikan, 2022)
The lack of information obtained by adolescents about puberty problems causes adolescents to not know what to do when menstruation occurs. The conduct of this study is to analyze the relationship between knowledge, attitudes, and sources of information on personal hygiene behavior during menstruation of adolescent girls at SMK Negeri V Buru Selatan, Maluku in 2022. Statistical analysis using the Chi Square test). The design of the study used a cross-sectional approach correlation. The population is all students of class X, XI and XII at SMK Negeri V Buru Selatan, Maluku in 2022 as many as 50 people. The results of the study found were that respondents had insufficient knowledge about personal hygiene during menstruation (95.7%). Student attitudes that support personal hygiene during menstruation (51.5%). Female students who have poor behavior regarding personal hygiene during menstruation (68.5%). The results showed that most respondents had good personal hygeine behavior as many as 34 respondents (68%), and those who had poor personal hygeine behavior as many as 16 respondents (32%). The results of bivariate analysis of all independent variables (knowledge, attitudes and suber information) p value are all < 0.05, or it can be concluded that there is a significant relationship between all independent variables (knowledge, attitudes and suber information) the p value of all < 0.05, or it can be concluded that there is a meaningful relationship (significant) between all independent variables (knowledge, attitudes and suber information) to hygeine's personal behaviour